Customer Retention: Atonement Oriented Recovery Strategies in the Retail Banking Industry in Malaysia - Yeop Yunus, Nek Kamal; M Goury, Arsalan; Abd Razak, Ahmad Zainal Abidin; Md Latip, Nor Azrin; Zainal Adnan, Ahmad Amri (Management Research Journal, 2017)
The service recovery and customer retention has caught the attention of researchers and academics recently. Despite the popularity of the subject, there were still not much known about how the service recovery strategies influenced customer retention in service organizations. Although service firms made the best effort, service failures were inevitable. Service recoveries were the efforts made by firms to bring back aggrieved customer to satisfaction. If recovery strategies were not prompt, proper and effective, the frustrating customers would defect to competitor. Thus, service firms were losing customers and revenues. Customer retention was vital and dominant key to business competitiveness and profitability. The present research tested two dimensions namely, economical and psychological atonement oriented recovery strategies. Data were collected by distributing the structured 58 item-questionnaires to 377 lecturers of Malaysian public universities randomly stratified. Results of the analysis found that all strategies were correlated with customer retention, except the customer oriented recovery strategies. Multiple regression analysis found that, the customer retention variance was explained by 50% of the service recovery strategies. The research has thrown some lights on the understanding of how service recovery strategies have influenced customer retention. Apart from that a new instrument has been developed. It was recommended that future research be conducted in legal services, business consultancy or educational services using such instrument which perhaps would yield more interesting result.